Monopoli dalam Perspektif Jarīmah Ta‘zīr (Studi Putusan di Komisi Pengawas Persaingan Usaha) - Makmun, Moh. (Fakultas Syariah IAIN Purwokerto, 2018)
This study is motivated by many cases of monopoly that cause consumer losses, and the absence of clear rules related to monopoly in the perspective of Islamic criminal law. The type of this research is field research using a comparative approach and the maqÄá¹£id al-syarÄ«â€˜ah approach (the purpose of Islamic law). The results of the study concluded that first, monopoly is contrary to Law No. 5 of 1999. Second, monopoly is contrary to the purpose of Islamic Shari'ah in the form of safeguarding property. Third, the monopoly in Islamic criminal law is a form of criminal offense because it violates the provisions of Islamic law, due to elements of fraud, engineering requests (offers), hoarding, cooperating in criminal acts, and inhibiting other business actors. In addition to the sanctions of monopoly actors according to Law No. 5 of 1999 in the perspective of Islamic criminal law are as follows: (1) administrative sanctions are in accordance with muamalah fiqh rules and basic legal rules; (2) the main criminal sanctions are in accordance with Islamic sharia provisions, but the sanctions need to be added by paying CSR as a return on profits; (3) additional criminal sanctions are also in accordance with the provisions of Islamic law; and (4) prisons are additional sanctions, not sanctions of choice.